1982
DOI: 10.1677/joe.0.0920293
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Rat Leydig Cells by Density Gradient Centrifugation

Abstract: A rapid method for preparing Leydig cells from rat testes is described. An interstitial cell suspension, prepared by collagenase treatment of decapsulated testes, was centrifugal for 10 min over a cushion of 60% (v/v) Percoll to remove red blood cells, and then centrifuged for 20 min in a 0-60% linear density gradient of Percoll. Seventy-four per cent of the cells present in that fraction of the gradient comprising 35-50% Percoll were Leydig cells; the yield from each testis was about 1.5 x 10(6) cells. The Le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

1983
1983
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…Previous studies have described two peaks of hCG binding in collagenase-dispersed interstitial cells from adult rat testes separated by Percoll density gradients (2,4,11,12,41). The density range covered by fractions II and III in the present study includes the more dense of these two peaks, which has previously been shown to consist predominantly of intact Leydig cells (4,11,12,(41)(42)(43). In a previous study using similar mild dissociation conditions, a second peak of hCG binding was observed in fraction IV, which contained intact Leydig cells (12).…”
Section: Discussionsupporting
confidence: 58%
“…Previous studies have described two peaks of hCG binding in collagenase-dispersed interstitial cells from adult rat testes separated by Percoll density gradients (2,4,11,12,41). The density range covered by fractions II and III in the present study includes the more dense of these two peaks, which has previously been shown to consist predominantly of intact Leydig cells (4,11,12,(41)(42)(43). In a previous study using similar mild dissociation conditions, a second peak of hCG binding was observed in fraction IV, which contained intact Leydig cells (12).…”
Section: Discussionsupporting
confidence: 58%
“…After washing twice, cells were resuspended in Medium-199 and 5 ml of interstitial cell suspension (20-25 109 cells/1) was layered on the top of each vial containing a previously prepared discontinÂŹ uous density gradient of Percoli (0-60% v/v), as described by Gale et al. (20), and then centrifuged at 800 g for 20 min at room temperature. The fractions were collected from the bottom of the tubes with a peristaltic pump and then washed twice with isotonic Medium-199 (1:1, v/v) to remove any residual Percoli.…”
Section: Methodsmentioning
confidence: 99%
“…Of the criteria available to identify a Leydig cell, it is only their characteristic morphology that is universally accepted as corresponding to the classical histological definition of these cells as described in 1850 by Leydig (22). Yet, in most studies, the histochemical demonstration of 3/3-hydroxysteroid dehydrogenase (3/5-HSD) (1, 3-6, 10-17, 19) or phenyl esterase (1,5), the presence of LH/hCG receptors (7,16,17) and, less frequently, the observation of yellow haloes seen with phase contrast microscopy (6)(7)(8) have each been considered acceptable markers for identification of isolated Leydig cells. Although limited morphological descriptions of en-PERCOLL GRADIENT SEPARATION OF MOUSE LEYDIG CELLS 1031 riched Leydig cell suspensions are available (1,2,4,6,14,15,17), details of the quantitative methods used to determine Leydig cell yield have not been given (2,6,14,15).…”
mentioning
confidence: 99%